Assessing the Awareness and Willingness of Mindanao State University Faculty, Staff, Alumni and Students in Contributing to a University-Based Zakat Fund - Salic, Jawad (EKOBIS SYARIAH, 2026)
In predominantly Muslim areas like Mindanao, universities have failed to institutionalise the zakat system in their institutional processes. Based on the construction of Islamic social finance and institutional trust that connects religious awareness and clear governance with donor willingness, this paper measures the feasibility of implementing zakat funds at Mindanao State University (MSU). This need is very urgent because a large number of students require financial assistance and a significant number of community members are eligible to distribute zakat. Meeting the descriptive survey research design with 314 respondents through stratified random sampling via Google Forms and analysed using descriptive statistics and weighted mean. This study assesses the level of knowledge among MSU stakeholders regarding the level of knowledge of the beneficiaries and their willingness to receive that knowledge, leading to the identification of key factors for success. The researchers established the university community has a high awareness of the religious value of zakat, a religious attitude towards that value, and trust in the institution. Three key elements highlighted by respondents who support the idea of a zakat fund at MSU are that the fund manages the use of discretionary funds in Islamic banking responsibly, integrates digital technology, and collaborates with Islamic scholars. Finally, the research paper recommends that MSU needs to adopt a Sharia-compliant zakat management system with a high level of transparency to set an example for other government organisations, thereby generating programs that can help student welfare and advance Islamic giving practices towards educational equity across the Philippines.